Mitigation strategies for waste elimination and cost reduction in the manufacture of Bowden cables - Koch, Luís; Gomes da Silva, Francisco José; Campilho, Raul Duarte Salgueiral Gomes; Vieira de Sá, José Carlos; Resende Lucas, Rafael [UNESP]; Sales-Contini, Rita de Cássia Mendonça (Springer Nature, 2025)
This study aims to describe a new approach to managing the reduction or elimination of cable end waste during the Bowden cable trimming operation in production lines since this waste represents thousands of meters of wasted cable per year, which is unsustainable from an economic and environmental point of view. This study has shown how the implementation of the DMAIC cycle (Define, Measure, Analyze, Improve, Control) in an automotive component industry can lead to a very significant reduction in material waste and, consequently, a reduction in the number of workers on certain assembly lines. Improvement actions were defined and implemented once the factors capable of eliminating and/or reducing cable trimming on the assembly lines had been identified. With the actions implemented, about the case study used for validation, an annual gain of approximately €89,289 has been achieved and a gain of €288,343 will be achieved by approximately 2026, after the elimination of trimming on five assembly lines and the reduction of trimming on eight assembly lines.
Keywords: Automotive sector; Bowden cable; DMAIC; Lean; Six Sigma